Sex Education Strategy for Elementary School Students as an Effort to Prevent Sexual Violence - Hamidaturrohmah; Suciati Cahyaningrum; Syafentina Maya Arinjani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to implement sex education strategies for elementary school students as an effort to prevent sexual violence. This research is a library research (Library Research) where the research results are obtained from data search, data selection, and data analysis by searching for nationally accredited journals through Google Scholar and then analyzed using descriptive qualitative techniques. The results of the literature review show that there is effectiveness in implementing sex education strategies as an effort to minimize sexual violence against children. Researchers recommend using 5M based on the results of the analysis that has been carried out including: 1) Providing information on sexual education as a student right, 2) Embedding underware rules (implementation of sex education) as part of school regulations, 3) Establishing cooperation with the local health office, 4) Establish cooperation with parents, and 5) Create sex education innovations